2013
DOI: 10.1083/jcb.2022oia57
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 interacts with Nrf2 to regulate antioxidant signaling and cell survival

Abstract: Oxidative stress plays an important role in cancer development and treatment. Recent data implicate the tumor suppressor BRCA1 in regulating oxidative stress, but the molecular mechanism and the impact in BRCA1-associated tumorigenesis remain unclear. Here, we show that BRCA1 regulates Nrf2-dependent antioxidant signaling by physically interacting with Nrf2 and promoting its stability and activation. BRCA1-deficient mouse primary mammary epithelial cells show low expression of Nrf2-regulated antioxidant enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 51 publications
(58 reference statements)
1
47
0
Order By: Relevance
“…Another gene which was shown to have ARE sequence in the BLAST analysis, RBBP8, has been reported to interact with BRCA1, a crucial protein involved in DSB repair and recombination. A recent study [35] has also reported the direct interaction of BRCA1 with Nrf2, in execution of cell survival functions. It would also be interesting to extend this study in normal cells, where the role of Nrf2 in DNA repair will have implication in radioprotection.…”
Section: Discussionmentioning
confidence: 93%
“…Another gene which was shown to have ARE sequence in the BLAST analysis, RBBP8, has been reported to interact with BRCA1, a crucial protein involved in DSB repair and recombination. A recent study [35] has also reported the direct interaction of BRCA1 with Nrf2, in execution of cell survival functions. It would also be interesting to extend this study in normal cells, where the role of Nrf2 in DNA repair will have implication in radioprotection.…”
Section: Discussionmentioning
confidence: 93%
“…1. (11,(22)(23)(24)(25)(26), and binding of competing proteins to Keap1 allowing increased activity of Nrf2 (27,28). Several mechanisms participate in the regulation of Nrf2 activity.…”
Section: Regulation Of Nrf2/are Signalingmentioning
confidence: 99%
“…Importantly, new insights have placed ROS as a key-factor in BRCA1-related breast cancers etiology due to BRCA1-NRF2 interaction and influence on NRF2-dependent antioxidant ability [24].…”
Section: Introductionmentioning
confidence: 99%